Effects of gas concentration and venting pressure on overpressure transients during vented explosion of methane–air mixtures. (1st July 2016) - Bao, Qi; Fang, Qin; Zhang, Yadong; Chen, Li; Yang, Shigang; Li, Zhan
Highlights: Four major overpressure transients were identified during explosion. Four typical Δ P – t profiles with different overpressure transients were detected. Occurrence & characteristics of peaks depended on concentration & venting pressure. Overpressure in chamber was nearly uniform during explosion. Abstract: 29 batches of vented explosion tests were conducted in a 12 m 3 concrete chamber filled with methane–air mixtures to investigate the effects of methane concentration and venting pressure on the development of overpressure inside the chamber. The deflagrations were vented from a square side window with a venting area of 0.64 m 2 upon rupture of the vent cover. The venting pressures were varied by using six different types of vent covers, and determined by performing a numerical simulation. Methane concentrations in the mixed gas varied between 6.5 and 13.5 vol.%, covering both lean and rich combustion regimes. The generation conditions of the four types of overpressure–time profiles with different overpressure transients were summarized. Among the overpressure transients, the Δ P 1 caused by failure of the vent cover and the Δ P 4 resulted from the coupling between acoustic mode and flame were basically dominant. The rate of Δ P 1 rise as well as peak value of Δ P 1 and Δ P 4 showed a same trend of first increasing and then decreasing with the methane concentration from lean to rich. They reached their maximum value at the methane concentration of about 9.5%, whereas the rate of Δ P 4 rise was found to be insensitive to the methane concentration. The peak value of Δ P 1 increased with the venting pressure, while that of Δ P 4 first increased and then decreased as the venting pressure increased. In addition, the rates of Δ P 1 and Δ P 4 rise were both insensitive to the venting pressure. The occurrence of Δ P 4 was depended on the methane concentration and the venting pressure. The differences in the behavior of these overpressure transients suggest their different generation mechanisms.